Analysis of laryngoscopic features in patients with unilateral vocal fold paresis. (9th December 2015) - Woo, Peak; Parasher, Arjun K.; Isseroff, Tova; Richards, Amanda; Sivak, Mark
Abstract : Objectives/Hypothesis: The diagnosis of paresis in patients with vocal fold motion impairment remains a challenge. More than 27 clinical parameters have been cited that may signify paresis. We hypothesize that some features are more significant than others. Study Design: Prospective case series. Methods: Two laryngologists rated laryngoscopy findings in 19 patients suspected of paresis. The diagnosis was confirmed with laryngeal electromyography. A standard set of 27 ratings was used for each examination that included movement, laryngeal configuration, and stroboscopy signs. A Fisher exact test was completed for each measure. A kappa coefficient was calculated for effectiveness in predicting the laterality of paresis. Results: Left‐sided vocal fold paresis (n = 13) was significantly associated with ipsilateral axis deviation, thinner vocal fold, bowing, reduced movement, reduced kinesis, and phase lag ( P < .05). Right‐sided vocal fold paresis (n = 6) was significantly associated with ipsilateral shorter vocal fold, axis deviation, reduced movement, and reduced kinesis ( P < .05). Using these key parameters, the senior author was accurately able to diagnose the side of paresis in 89.5% of cases for a kappa coefficient of 0.78. Conclusions: Of the multiple features on laryngoscopy, glottic configuration, ipsilateral thin vocal fold, vocal fold bowing, reduced movement, reduced kinesis, and phase lag were more likely to be associated with vocal fold paresis. Level of Evidence: 4 Laryngoscope, 126:1831–1836, 2016